Screening and evaluation of purines-degrading lactic acid bacteria isolated from traditional fermented foods in Yunnan Province and their uric acid-lowering effects in vivo - Liu, Zhen; Zou, Xing-Yuan; Yue, Jiang; Li, Shan; Ou, Xia; Huang, Chuang; Liu, Chen-Jian; Li, Xiao-Ran (Frontiers in Microbiology, 2025)
IntroductionTraditional fermented foods have recently been recognized for their potential benefits in managing hyperuricemia (HUA) and gout.MethodsThis study evaluated the purine degradation ability of seventy-eight lactic acid bacteria (LAB) isolated from traditional fermented foods in Yunnan Province, China, by HPLC. The possible mechanisms of in vitro purine degradation were explored through whole-genome sequencing, comparative genomics, and qRT-PCR, and the effect of the LAB on HUA in SD rats was verified.Results and DiscussionIn vitro results demonstrated that Limosilactobacillus fermentum MX-7 and GL-1-3L exhibited high degradation ratios for guanine, while Pediococcus acidilactici GJ09-3-7L showed good potential in degrading xanthine. All three strains were also effective in degrading inosine and guanosine. And the genomes of all three strains contained a high number of enzymes related to purine metabolism, transporter and permease. In vivo results suggested that the MX-7 strain not only lowering serum uric acid (UA) and urea nitrogen levels in HUA SD rats but also providing a protective effect on renal function. These findings indicate that the MX-7 strain could serve as a promising adjunctive therapy for treating HUA.